The Brethren - Haggard, H. Rider (Henry Rider), 1856-1925 (Salt Lake City, UT : Project Gutenberg, 2001)
"The Brethren" by H. Rider Haggard is a historical novel written during the late 19th century. It explores themes of chivalry, love, and the intense conflicts between the Crusaders and the Saracens in the Holy Land during the era of the Crusades. The narrative centers around two young knights, Godwin and Wulf D'Arcy, twins of noble blood, as they navigate love and loyalty in a world rife with warfare and impending doom. The story unfolds their relationship with Rosamund, their cousin, set against the backdrop of their encounters with the formidable Sultan Saladin and the romantic tensions surrounding their quest for honor and love. The opening of "The Brethren" introduces vivid characters and emotional stakes through a tapestry of relationships and impending conflict. It begins with a dedication where Haggard reflects on the nature of imagination and romance before moving into a prologue that hints at the struggles between the Christian and Muslim forces in the Holy Land, and the dreams of Saladin, who contemplates capturing his long-lost niece, Rosamund. As the narrative transitions to the first chapter, we are introduced to Rosamund, Godwin, and Wulf at Death Creek, where an ambush forces the brothers to defend her against masked attackers$1 (Btheir bravery revealing a blend of personal and national honor. The strong bonds and rivalries set within themes of love and duty effectively lay the groundwork for the intricate plot that Haggard weaves, promising readers an engaging historical adventure filled with emotion and action. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Brethren_(Haggard_novel)
Release date is 2001-08-01
JoAnn Rees
Keywords: Great Britain -- History -- Medieval period, 1066-1485 -- Fiction; Arab countries -- Fiction; Crusades -- Fiction